Xenophon and the Cynegeticus: the construction of the ideal Greek hunter - do Amaral Biazotto, Thiago (Revista Archai, 2023)
Starting from the hunting treatise Cynegeticus, assigned to Xenophon, this article seeks to reflect on the way in which the construction of the ideal hunter of the polis described by the Attic author. This aim will aboard both practical terms - equipment, prey, methods of hunting conducting etc - and moral terms, taking in account the numerous attacks made against the sophists throughout the booklet. To accomplish this aim, the present text includes a brief recapitulation of Xenophon’s life, the most important historiographical interpretations on the Cynegeticus and its dating, and, finally, the way in which the Attic author describes his ideal Greek hunter.